MANAGING HUMAN FACTORS IN IMPLEMENTING ELECTRONIC DOCUMENT SYSTEM IN THE PUBLIC SECTOR - TOMS LEIKUMS (Challenges of the Knowledge Society)
Document management underlies the activities of almost every organization. Correctly managed correspondence and organized document circulation characterize successful performance particularly in the public sector organizations. Even though production of documents itself is not the main task of governmental institutions, document creation and processing are crucial processes for the provision of basic functions in public sector. In the 21st century it gets more important to use the new possibilities offered by modern technologies, including electronic document management. Public sector itself is a heavy bureaucratic apparatus in the need of elasticity and ability to change its working processes and habits in order to gradually switch to the digital environment. Western European countries have already turned to electronic document management whilst most of the Eastern European countries, including Latvia, have just recently started a gradual electronization of document circulation. When implementing electronic document management systems in the public sector organizations, it often comes to resistance of the staff and unwillingness to change the accustomed methods of work – paper format document circulation. Both lower level staff and higher level managers put obstacles to electronic document management. In this article author inspects cases of successful practice and analyses possible action mechanisms that could convince public sector personnel of advantages of electronic document circulation and prepare them to switch to work with digital documents.